Produção de sementes e comportamento germinativo de Tibouchina clavata (Pers.) Wurdack. (Melastomataceae) - Prudente, Claudia Mascagni; Sader, Rubens [UNESP]; Barbosa, José Marcos; Dos Santos Junior, Nelson Augusto (My University, 2012)
In the process of riverine forest restoration, increasing emphasis has been given to the study of herbaceous and shrub species. However, for many of these we still lack basic knowledge, such as reproduction biology. Therefore, the objective of this study was to characterize the production, seed germination and reproductive capacity of Tibouchina clavata (Pers.) Wurdack., a species of wide distribution in wetlands. Fruits were collected from different mother trees located on the southern coast of São Paulo state and, after processing, were subjected to germination under constant temperatures of 25 and 30°C, and alternated temperatures of 25-30°C in the first essay, and at 15, 20, 25, 30, 35, 40°C in another essay, and at 25 °C with presence or absence of light. 10 plants were marked and, in each one, the number of fruits per plant and seed number per fruit were determined to characterize their reproductive capacity. The species germinates over a wide temperature range (15 to 35 °C), and the optimum temperature was in the range of 20 to 30 °C. Seed didn't germinate at 40 °C and could be characterized as being of absolute positive photoblastism. In general, there were over 1600 seeds per fruit and 85.000 seeds per plant. The high seed yield, coupled with good germination percentage demonstrated that this is a species with high reproductive potential.
Seeds production and germination of Tibouchina clavata (Pers.) Wurdack. (Melastomataceae)
Keywords: Colonizing species seeds; Restoration of sandbank forest; Colonizing species; Constant temperature; Forest restoration; Optimum temperature; Reproductive capacity; Reproductive potential; Seed germination; Seed number; Seed yield; Shrub species; Temperature range; Conservation; Cultivation; Forestry; Fruits; Plants (botany); Restoration; Seed